Migrant screening: Lessons learned from the migrant holding level at the Greek–Turkish borders. Issue 2 (March 2017) - Eonomopoulou, Assimoula; Pavli, Androula; Stasinopoulou, Panagiota; Giannopoulos, Lambros A.; Tsiodras, Sotirios
Summary: In March 2011, a migrant health project became operational that aimed to provide medical and psychosocial support to migrants at the Greek–Turkish border. The aim of this study is to describe common syndromes, the communicable disease profile and vaccination patterns in newly arrived migrants through a surveillance system that was based on medical records data as well as screening procedures. Data were collected prospectively using one standardized form per patient including demographic information, civil status, and medical and vaccination history. A tuberculin screening test (TST) and serological testing for HIV, hepatitis B and hepatitis C were performed after obtaining informed consent. A total of 6899 migrants were screened, the majority of whom were male (91%) and 18–31 years old (85%), with a mean age of 25.3 years. Of all patients, 2.5% received secondary care. Common complaints and diagnoses included respiratory infections (23%) and myalgia (18%). The tuberculin screening test (TST) was positive in 7.8% out of 1132 patients tested. Out of 632 migrants, 0.3%, 3.2% and 0.8% tested positive for HIV, hepatitis B and hepatitis C, respectively. Overall, 22.3% of adults were vaccinated against poliomyelitis. Irregular migrants that enter Greek borders are generally in good health. Nevertheless, the risk of spreading communicable diseases is an important issue to consider among migrants at the holding level due to severe overcrowding conditions. Therefore, there is a need to strengthen surveillance and implement harmonized screening procedures with the aim of providing sustainable and good quality services that are focused on prevention and early treatment.